2016
DOI: 10.1002/jwmg.21102
|View full text |Cite
|
Sign up to set email alerts
|

Identification of robust microsatellite markers for wild pig fecal DNA

Abstract: Collection of fecal samples for use in a genetic capture-mark-recapture framework has become popular as a noninvasive method of monitoring wildlife populations. A major caveat to this process, however, is that fecal samples often yield low quality DNA that is prone to genotyping errors, potentially leading to biases in population parameter estimation. Therefore, considerable care is required to identify robust genetic markers, especially in hot or humid conditions that may accelerate DNA degradation. We identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…We collected fecal material as either fresh scat collected from transects within 24 hr of defecation following the methodology of Kierepka et al. () (California; 19 individuals) or from fecal material taken directly from the colon of culled individuals (Texas and Florida; 14 and 15 individuals, respectively). California samples were collected from 31 July 2014 through 3 September 2014 and immediately placed on ice in the field, then frozen.…”
Section: Methodsmentioning
confidence: 99%
“…We collected fecal material as either fresh scat collected from transects within 24 hr of defecation following the methodology of Kierepka et al. () (California; 19 individuals) or from fecal material taken directly from the colon of culled individuals (Texas and Florida; 14 and 15 individuals, respectively). California samples were collected from 31 July 2014 through 3 September 2014 and immediately placed on ice in the field, then frozen.…”
Section: Methodsmentioning
confidence: 99%
“…Elevation of the SRS ranges from 30-115 m above sea level. Climatic conditions of the SRS are described in Kierepka et al 71 and are generally characterized by warm temperatures and high humidity. Wild pigs have been lethally controlled at the SRS since 1952 in an effort to mitigate damage 72 .…”
Section: Methodsmentioning
confidence: 99%
“…We collected fecal samples along transects every other day for 12 days for a total of 6 sampling occasions per study site. Research by Kierepka et al 71 demonstrated that accurate genotypes could be attained from wild pig fecal samples with five days of environmental exposure, excluding rain; therefore, our sampling scheme should be minimally affected by exposure issues. As in Ebert et al 62 , we employed a modified adaptive cluster sampling protocol, which is a method designed to help detection of rare but clustered samples, described in 73 to maximize collection of fecal samples and account for social behavior of wild pigs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…qPCR has the additional benefit of providing quality control to select optimal DNA samples for further analysis, such as sequencing and genotyping, thus allowing researchers to avoid wasting resources on poor‐quality samples that are unlikely to yield results. Kierepka et al () used qPCR to screen feral pig Sus scrofa faecal‐derived DNA prior to genotyping, to generate a robust capture–mark–recapture protocol in order to facilitate accurate estimates of abundance.…”
Section: Detection and Monitoringmentioning
confidence: 99%